Alteration of ecosystem structure by a burrowing herbivore, the plains vizcacha (Lagostomus maximus) - Villarreal, Diego (2008)
Although the role of animals in altering ecosystem structure and dynamics has received increased attention in the last decade, large gaps in knowledge still exist, limiting our ability to incorporate animals into models of ecosystem dynamics. Our research on the plains vizcacha (Lagostomus maximus, family Chinchillidae), a colonial burrowing herbivore in grasslands and semiarid scrub of southern South America, addresses 3 of these gaps - belowground impacts of vertebrates on soils, net effects of multiple types of animal activities on ecosystem structure, and the scaling up of plot-level effects to the landscape. Our study demonstrated that grazing by vizcachas produced strong spatial patterns in composition, biomass, and nutrient pools in herbaceous vegetation. In burrows, total nitrogen (N), total phosphorus (P), and inorganic N were greater than in undisturbed soil at a similar depth. Burrow soil and foliage of shrubs growing on burrows were depleted in 15N, reflecting the signature of vizcacha feces. Transport of caliche by vizcachas resulted in significantly greater P concentrations in surface soil on burrows. Indirect effects of vizcachas on shrubs, through alteration of soil nutrients, transport of caliche to the soil surface, and possibly altered fire regimes, resulted in greater biomass, foliar N and P content, and total N and P pools in shrubs. Net effects of vizcachas on ecosystem structure, above- and belowground, are spatially extensive, and likely persist much longer than the colonies of vizcachas that generated these effects. This study demonstrates that the largest impacts of herbivores on ecosystem structure can be through their effects on plants they do not consume and, in systems where biopedturbation is frequent, animal transport is among the key processes that determine vertical distribution of nutrients in the soil profile.